2022
DOI: 10.7759/cureus.29458
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss: A Review

Abstract: The objective of this review is to present and evaluate the current views on sudden sensorineural hearing loss. Sudden sensorineural hearing loss is an otolaryngology emergency requiring immediate diagnosis and treatment. The etiology of the majority of cases is unknown. The etiology can be classified into various categories such as autoimmune diseases, infections, functional, metabolic disorders, vascular disorders, traumatic causes, due to toxins, and neurological disorders. We searched the U.S. National Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The inner ear is especially sensitive to the blood supply, which is regulated by adrenergic receptors, plasma viscosity, and platelet function ( 2 ). Supplied by two tiny arteries at the end, the cochlea is vulnerable to damage due to several important factors, such as the small diameter of the arteries and the absence of arterial branches ( 10 ). The obstruction of blood flow of the labyrinthine artery or its origins for more than 1 min would lead to irreversible damage to audio-vestibular function ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inner ear is especially sensitive to the blood supply, which is regulated by adrenergic receptors, plasma viscosity, and platelet function ( 2 ). Supplied by two tiny arteries at the end, the cochlea is vulnerable to damage due to several important factors, such as the small diameter of the arteries and the absence of arterial branches ( 10 ). The obstruction of blood flow of the labyrinthine artery or its origins for more than 1 min would lead to irreversible damage to audio-vestibular function ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cofactors including the average age, gender distribution, and the distribution of auditory types and hearing degrees in the three groups were inequivalent, so we analyzed the efficacy of SSNHL patients with different audiogram-type SSNHL. It is reported that comparing patients with other types of audiometric curves, patients with low-frequency hearing loss may have a better prognosis ( 1 , 17 ). In 2015, a Chinese multicenter study showed that the curative rate of patients with low-frequency hearing loss could be as high as 90.73%, whereas, in patients with high-frequency hearing loss, the number was only 65.96% ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Created with BioRender.com Specifically, western blot analysis in these patients has revealed the presence of antibodies against cochlin and β-tectorin, which are distributed across various regions in the inner ear, such as the spiral limbus, spiral ligament, basal hair cells, supporting cells, cochlear, and vestibular labyrinths [16,17]. Additionally, other proteins like Kresge Hearing Research Institute-3 (KHRI-3), expressed in the wall of the saccule, utricle, endolymphatic sac, supporting cells, as well as type II collagen, expressed in the subepithelial layer of the endolymphatic duct and the spiral ligament, could also be potential targets in immune-mediated hearing loss [18]. The inner ear contains hair cells that are responsible for converting sound vibrations into electrical signals, which are then transmitted to the brain for interpretation.…”
Section: Pathophysiology Of Inner Ear Diseases In Autoimmune and Auto...mentioning
confidence: 99%